Pengaruh Umur Listing, Leverage, Profitabilitas dan Reputasi Auditor Terhadap Internet Financial Reporting : Pada Perusahaan Manufaktur yang Terdaftar Di Bursa Efek Indonesia Tahun 2018 - Gabriela Madeleine Nurani R; Sri Hanggana (SEKOLAH TINGGI ILMU EKONOMI NGANJUK, 2020)
This Study aims to examine the effect between listing age, leverage, profitabillity, and auditor reputation on internet financial reporting by manufacturing firms listed on official market of the Indonesian Stock Exchange (ISE) 2018. The final data collected for this study is a total of 125 samples over a year. Data analysis in this study used multiple regression analysis. The results indicate a significant positive association between auditor reputation and internet financial reporting. However the firm age, leverage, and profitabillity do not have a significant association on internet financial reporting.